2010
DOI: 10.1186/1478-4505-8-30
|View full text |Cite
|
Sign up to set email alerts
|

Societal output and use of research performed by health research groups

Abstract: The last decade has seen the evaluation of health research pay more and more attention to societal use and benefits of research in addition to scientific quality, both in qualitative and quantitative ways. This paper elaborates primarily on a quantitative approach to assess societal output and use of research performed by health research groups (societal quality of research). For this reason, one of the Dutch university medical centres (i.e. the Leiden University Medical Center (LUMC)) was chosen as the subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 24 publications
(19 reference statements)
0
27
0
Order By: Relevance
“…An emerging science of “societal impact assessment” seeks to categorize and measure both the various interactions between university academics and other stakeholders and the outputs and outcomes emerging from them . The European Seventh Framework Programme, for example, sought to assess synergies with science education, engagement with civil society and policymakers, dissemination to the general public in multiple languages, and the employment consequences of the research .…”
Section: Mode 2: From “Knowledge Translation” To “Knowledge Production”mentioning
confidence: 99%
“…An emerging science of “societal impact assessment” seeks to categorize and measure both the various interactions between university academics and other stakeholders and the outputs and outcomes emerging from them . The European Seventh Framework Programme, for example, sought to assess synergies with science education, engagement with civil society and policymakers, dissemination to the general public in multiple languages, and the employment consequences of the research .…”
Section: Mode 2: From “Knowledge Translation” To “Knowledge Production”mentioning
confidence: 99%
“…Dissemination in the public sphere counts publication and dissemination activities via other channels than academic books or articles. This indicator of publication count is just one of the indicators suggested by Mostert et al (2010) in their questionnaire tool to measure societal relevance which also includes standardised weighting schemes to accommodate certain activities in the field the researcher is active in. All the aforementioned counting methods assume an equal distribution of contribution across all authors of a publication.…”
Section: Publication Count Categorymentioning
confidence: 99%
“…14 This study found that entrepreneurial output is not significantly related to academic output. A study of societal quality in a UMC in the Netherlands (Mostert et al 2010) showed no relationship between societal and scientific quality. Finally, a French study (Jensen et al 2008) examined the relationship between popularisation activities (e.g.…”
Section: Societal and Scientific Productivitymentioning
confidence: 99%